Novel and potential application of cryopreservation to plant genetic transformation - Wang, Biao; Zhang, Zhibo; Yin, Zhenfang; Feng, Chaohong; Wang, Qiaochun (Biotechnology advances, 2012)
The world population now is 6.7billion and is predicted to reach 9billion by 2050. Such a rapid growing population has tremendously increased the challenge for food security. Obviously, it is impossible for traditional agriculture to ensure the food security, while plant biotechnology offers considerable potential to realize this goal. Over the last 15years, great benefits have been brought to sustainable agriculture by commercial cultivation of genetically modified (GM) crops. Further development of new GM crops will with no doubt contribute to meeting the requirements for food by the increasing population. The present article provides updated comprehensive information on novel and potential application of cryopreservation to genetic transformation. The major progresses that have been achieved in this subject include (1), long-term storage of a large number of valuable plant genes, which offers a good potential for further development of novel cultivars by genetic transformation; (2), retention of regenerative capacity of embryogenic tissues and protoplasts, which ensures efficient plant regeneration system for genetic transformation; (3), improvement of transformation efficiency and plant regeneration of transformed cells; (4), long-term preservation of transgenic materials with stable expression of transgenes and productive ability of recombinant proteins, which allows transgenic materials to be stored in a safe manner before being analyzed and evaluated, and allows establishment of stable seed stocks for commercial production of homologous proteins. Data provided in this article clearly demonstrate that cryo-technique has an important role to play in the whole chain of genetic transformation. Further studies coupling cryotechnique and genetic transformation are expected to significantly improve development of new GM crops.